Minimal incision approach for abdominal aortic aneurysm (AAA) repair - Laohapensang K. (2014)
To evaluate the appropriate use of the minimal incision aortic surgery (MIAS) approach in nonruptured infrarenal abdominal aortic aneurysm (AAA) repair, we prospectively compared the MIAS approach with the transperitoneal approach (TPA). Eighteen patients in whom the MIAS was used and 18 who had the TPA during the same period were included in this study. There was a significant difference in intraoperative fluid needs (2050 ± 510, MIAS; 3500 ± 300, TPA) and estimated blood loss (ml) (855 ± 316, MIAS; 1246 ± 615, TPA) between the two groups. The MIAS approach had a shorter intensive care unit (ICU) stay (1 d vs. 2.4 d), hospital stay (8.3 d vs. 14.5 d), quicker return to general dietary feeding (2 d vs. 6.9 d), and less morbidity (23.5% vs. 77.7%) than the TPA group. The MIAS group had a smaller total cost payment than the TPA group (US$ 3,000 ± 150 vs. US$ 3,750 ± 200) because of less complications, shorter ICU, and shorter hospital stay. Our findings indicated that MIAS is a safe, effective, and suitable method for nonruptured infrarenal AAA repair.